Praktek Akad Mukhabarah Berbasis Adat Lokal (Studi Kasus di Pariangan Kabupaten Tanah Datar) - Rita Masdar; Rizal Rizal (YUME : Journal of Management, 2026)
This study aims to analyze the practice of mukhabarah in agricultural cooperation and to assess its conformity with the principles of fiqh muʿāmalah and Islamic economic justice. The research employs a qualitative approach with a descriptive-analytical design. Data were collected through fourteen in-depth interviews with tenant farmers, landowners, and community leaders, and were supported by field observations and literature review. Data analysis was conducted using the interactive analysis model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings indicate that mukhabarah practices in the field are generally carried out informally without written contracts, with profit-sharing mechanisms that are not clearly agreed upon from the outset and risk-sharing arrangements that tend to place a disproportionate burden on tenant farmers. This condition reflects a gap between the normative concept of mukhabarah in fiqh muʿāmalah and the empirical realities of agricultural practices. From the perspective of Islamic economic justice and maqāṣid al-sharīʿah, mukhabarah practices have not yet fully functioned as instruments for economic protection and empowerment of tenant farmers. This study underscores the importance of a contextual approach in evaluating sharia-based contracts, so that they are not only formally valid but also substantively just